DIGITAL TRANSFORMATION OF SAUDI ARABIA’S BANKING: A COMPARATIVE STUDY - Hariri, Mohammad (International Journal of Islamic Banking and Finance Research, 2023)
Banks’ digital transformation has become a growing and competitive research area in the last decade. This study aims to compare the digital transformation of the Saudi banking sector with that of developed and emerging Islamic countries by examining progress, digital solutions to banking services provided, and regulatory frameworks. To this end, a systematic review was conducted, analyzing 44 primary documents and seven websites collected through a 5-step process: scoping, planning, searching, selection, and eligibility. Next, a comparative analysis of these documents was conducted, analyzing the similarities and differences of the digital transformation processes addressed by Saudi Arabia, the U.S., the United Kingdom, and Malaysia. The findings revealed that Saudi Arabia and Malaysia have banking sectors of similar size, smaller than those of the U.S. and the U.K., although all of these sectors are of significant importance in the economies of their respective countries, as measured by their share in GDP. All countries have adopted similar digital technologies and offer very similar banking services. Concerning its regulatory frameworks, the U.K.’s sandbox approach is the most effective and inspiring. At the same time, the U.S. needs to catch up due to its regulatory complexities and differences in approach between federal and state jurisdictions. For their part, Saudi Arabia and Malaysia have developed their regulatory frameworks with approaches inspired by the U.K. model, although both differ in the degree of Sharia compliance. JEL Classification Codes: G21, G28, L86, O33, O57.